Closing and cloning in open-end mutual funds - Chen, Hsiu-Lang; Gao, Sheldon; Hu, Xiaoqing (Journal of Banking & Finance, 2012)
Using a unique dataset, we document that only those closed funds for which no new fund is subsequently launched continuously deliver positive abnormal returns. This suggests the existence of an optimal fund scale. In spite of the potential diseconomies of scale, a non-trivial proportion of closed funds have new funds cloned—the scale motive would not be a complete explanation for the closure. When managers of closed funds clone new funds, they receive greater public attention and thus can attract more fund flows and charge higher fees. Furthermore, better-performing closed fund managers attract more fund flows to their new siblings, making the closure an effective mechanism to extract economic rents. Overall, we find that closing and cloning is an attractive strategy for funds seeking to increase their management fees and funds with more managers in place. Aspects of the closed fund family also affect the launch decision of new siblings.